Timing and predictive factors to develop chronic kidney disease in children with idiopathic nephrotic syndrome - Idris, Siti Salamah Mohd (2017)
Introduction: Idiopathic nephrotic syndrome (INS) is the commonest type of nephrotic syndrome in children and majority has favourable outcomes. A small proportion of INS would progress to chronic kidney disease (CKD). We investigated the timing and predictive factors associated with progression of CKD in this children. Methods: A retrospective record review was used to investigate the demographic variables, biochemical and histological changes in children with INS aged 12 months to 18 years old from 2001-2016 in Hospital Universiti Sains Malaysia (Hospital USM). The median renal survival time to progress to CKD III or higher was determined using survival curve analysis. Multiple cox regression was used to identify predictive factors related to outcomes to CKD. Results: The total of subjects were 112 enrolled (male =71, female= 41) and majority was steroid sensitive type. Ten percents of INS progressed to CKD III or higher. The median renal survival time in steroid-resistance nephrotic syndromes (SRNS) was 13 years. Focal segmental glomerulosclerosis (FSGS) was predominant in SRNS type. The predictors to progression to CKD were steroid-resistance type (adjusted HR: 23.8, 95% CI 2.8- 200.9) and the presence of hypertension at presentation (adjusted HR: 8.1, 95% CI 1.2- 55.7). Conclusion: The median renal survival time was comparable to other studies but SRNS type and the presence of hypertension at presentation were the main predictors to develop CKD in our population